Hubungan Pola Makan dan Aktivitas Fisik dengan Kejadian Premenstrual Syndrome (PMS) pada Remaja Putri - Andicha Gustra Jeki; Siti Fati Hatussaadah; Tina Yuli Fatmawati; Liya Putri Rahmaniya; Ike Fitria Isnai; Gusni Ajeng Dwisari (Prosiding Seminar Kesehatan Nasional, 2025)
Premenstrual Syndrome (PMS) is collection of physical, psychological, and behavioral symptoms that occur before menstruation and can disrupt daily activities, especially in adolescent girls. Poor diet and low physical activity are two lifestyle factors that can trigger or worsen PMS symptoms. This study aims to determine the relationship between diet and physical activity with the incidence of PMS 10th grade female adolescents at SMK Fania Salsabila, Jambi City. The method used is quantitative study with crosssectional approach. Total 60 respondents were selected using proportional random sampling techniques from total population 120 female students. The study was conducted in May 2025. Data were collected using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), Global Physical Activity Questionnaire (GPAQ), and Shortened Premenstrual Assessment Form (SPAF). Data analysis was carried out univariately and bivariately using the Chi-Square test. The results of the study showed that the majority of respondents had poor eating patterns, namely 45 respondents (75.0%), low physical activity levels were 38 respondents (63.3%), and severe PMS symptoms were 29 respondents (48.3%). There was a significant relationship between eating patterns and the incidence of PMS (p < 0.05), as well as between physical activity and the incidence of PMS (p < 0.05). It can be concluded that adolescents with unhealthy eating patterns and low physical activity have higher risk of experiencing PMS with moderate to severe symptoms. This study recommends health education and school-based interventions regarding the importance of healthy lifestyle to prevent or reduce the impact of PMS on adolescents.